Pengaruh Kompensasi, Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Daxen Indonesia - Reni Indriyani; Andriansyah Bachtillah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the influence of compensation, leadership and work discipline and its impact on employee performance. Population in this search is 36 employee of PT. Daxen Indonesia. The sample used is the entire of population. The sampling method uses saturated sampling because the population is <100 respondents. Data collection methods using survey methods with research instruments is a questionnaire. The data analysis method uses SPSS23 program assistance. This study proves that compensation has a significant effect on employee performance. Leadership has a significant effect on employee performance. Work discipline has a significant effect on employee performance.